GIS Application for Determining Geographical Factors on Intensity of Erosion in Serbian River Basins. Case Study: The River Basin of Likodra - Branko Ristanović; Marija Cimbaljević; Đurđa Miljković; Miloš Ostojić; Renata Fekete (Atmosphere, 2019)
Inadequate management of water resources may generate various potential geohazard risks. To resolve potential risks, significant anthropogenic factors need to be engaged, such as human, material and financialcapacities. Fluvial erosion and soil erosion control are among the major problems that occur within an integrated water management system. These natural processes can be accelerated due to certain human activities: agricultural production, civil engineering and mining. Is there a comprehensive approach that would identify the problems at the early stages and minimize the necessary actions? The application of the geographic information system (GIS) within the modified Gavrilović model represents a step further towards systematic monitoring and regulation of watercourses in different parts of the basin. This case study provides an example of the early detection of hydrological problems that can occur in a river stream and a proposal for the solutions that would be imposed as the logical causality based key. The Likodra river basin is a representative example of the application of GIS for early detection and prevention of current water problems.